Use of firewood for artisanal ceramic production in a context of forest scarcity in Northeastern Brazil - da Silva, Maria Madelena Soares; Feitosa, Ivanilda Soares; Cruz, Ramon Salgueiro; de Sá, Vânia Aparecida; de Medeiros, Patrícia Muniz; da Silva, Rafael Ricardo Vasconcelos (Ethnobiology and Conservation, 2023)
In this study, we sought to examine firewood use patterns in artisanal ceramic production by a quilombola community in the context of forest scarcity in Northeastern Brazil. This article aimed to answer the following questions: (1) Is the firing of ceramic products related to the perceived quality, diversity, or plant part used as firewood? (2) Does the diversity of plants used as firewood vary according to the age and gender of artisan potters? (3) What are the physical and energetic properties of the species most commonly used as firewood? Our main findings were that resource availability and accessibility seem to be the determining factors of firewood use. Exotic species were widely used. Variables commonly described as predictors of firewood diversity, such as age and gender, were not relevant in the context of forest scarcity. The most used exotic species have good physicochemical properties and can be a viable alternative to meet the firewood demand of ceramic production. However, the results showed that these species are more readily available to potters who have access to private woodlands. Therefore, in the studied context, we suggest the need for conservation strategies that foster the creation of energy forests composed of exotic species and, in parallel, promote conservation and reforestation actions aimed at native species.